Operation mode performance and optimization of a novel coupled air and ground source heat pump system with energy storage: Case study of a hotel building. (December 2022) - Wang, Yubo; Quan, Zhenhua; Zhao, Yaohua; Wang, Lincheng; Jing, Heran
Abstract: The problem of soil heat imbalance in traditional ground source heat pump (GSHP) systems in cold regions hinders the utilization of geothermal energy. This paper takes a hotel building energy supply system as an example to study the feasibility of a coupled air and ground source heat pump system with energy storage. The design intention of the proposed system was to add an air source heat pump (ASHP) and a water source heat pump (WSHP) as auxiliary heat sources to undertake part of the energy supply function of a GSHP. In winter, the system uses the ASHP as the low temperature heat source of the WSHP, so that its heating performance is basically not affected by extremely low outdoor temperatures, with an average system COP of 2.3. Combined with the energy storage (cold and heat storage), the "peak load shifting" of the power grid and the minimization of the system operation cost are realized. The simulation model of the novel system is established and verified by the monitoring data of the system. The operation mode is optimized to maximize the COP of the system, and the defrosting mode of the ASHP and soil heat balance were analyzed. The results show that the optimized defrosting control can increase the heating capacity of the ASHP by 13.9%. In addition, the proposed system can not only maintain the soil heat imbalance rate to 2.6%, but also reduce the operating cost. The calculation shows that compared with the traditional GSHP system, the annual operation cost of the novel system is only 58%, and the carbon emission can be reduced by 7.14%, which has good economic and environmental benefits. The popularization and application of this form of building system in cold regions has a high value. Graphical abstract: Image 1